2008
DOI: 10.1111/j.1365-2966.2008.13098.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact cratering and the Oort Cloud

Abstract: We calculate the expected flux profile of comets into the planetary system from the Oort Cloud arising from Galactic tides and encounters with molecular clouds. We find that both periodic and sporadic bombardment episodes, with amplitudes an order of magnitude above background, occur on characteristic time‐scales ∼25–35 Myr. Bombardment episodes occurring preferentially during spiral arm crossings may be responsible both for mass extinctions of life and the transfer of viable microorganisms from the bombarded … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…For a quarter of a century, evidence that confirms the existence of real periodicity in these catastrophic events has been published, e.g. by Stothers (1998), Moon et al (2003), Yabushita (2004), Chang & Moon (2005), Stothers (2006) and Wickramasinghe & Napier (2008). Evidence against such periodicity has also been presented, e.g.…”
Section: Introductionmentioning
confidence: 74%
“…For a quarter of a century, evidence that confirms the existence of real periodicity in these catastrophic events has been published, e.g. by Stothers (1998), Moon et al (2003), Yabushita (2004), Chang & Moon (2005), Stothers (2006) and Wickramasinghe & Napier (2008). Evidence against such periodicity has also been presented, e.g.…”
Section: Introductionmentioning
confidence: 74%
“…Since then, several authors have claimed that there is a significant periodic signal present, but the periods differ quite a lot from study to study. The signal is the most prominent for 40 large, well‐dated craters that are up to 250 Myr old (Napier 2006), but the period is difficult to measure, with estimates of between 24 and 26 Myr (Napier 2006), 30 Myr (Napier 2006; Stothers 2006), 36 Myr (Napier 2006; Stothers 2006), 38 Myr (Yabushita 2004; Wickramasinghe & Napier 2008) and 42 Myr (Napier 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The multibody dynamics involved in putting these on a collision course with the Earth implies that cratering is a random phenomenon, but the rate of impacts is not necessarily constant in time. It has been suggested that gravitational perturbations of the Oort cloud due to the Galactic tide, passages of the Solar system near to molecular clouds, or an unseen solar companion, may send large numbers of comets into the inner Solar system as a comet shower, increasing the impact rate (Davis, Hut & Muller 1984; Rampino & Stothers 1984; Torbett & Smoluchowski 1984; Napier 1998; Wickramasinghe & Napier 2008; Gardner et al 2011). Simple dynamical calculations indicate that the Sun oscillates vertically about the Galactic mid‐plane with a period of 52–74 Myr, depending on the mass density assumed (Bahcall & Bahcall 1985; Shuter & Klatt 1986; Stothers 1998).…”
Section: Introductionmentioning
confidence: 99%